PENGARUH PROGRAM MBKM TERHADAP KESIAPAN KERJA MAHASISWA DI LINGKUNGAN UNIVERSITAS PADJADJARAN - Muhamad Faqih; Solehudin Solehudin; Nunung Nurhasanah (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2024)
This research aims to determine the influence of the MBKM work program on students' work readiness at Padjadjaran University and it is hoped that this MBKM program will have a good influence on students who take part in the program, as well as being the first step to prepare students to face the real world of work. One of the programs carried out by the Ministry of Education, Culture, Research and Technology (Kemendikbud Ristek) of the Republic of Indonesia is Merdeka Belajar Kampus Merdeka (MBKM), which is the latest innovation launched to transform the education system in Indonesia. MBKM aims to produce better and more relevant graduates so that they can increase knowledge, train skills and develop professional attitudes in students. The method used in carrying out this research was by filling out a questionnaire via Google form, then the data obtained was analyzed using a statistical approach. The statistical analysis used is instrument tests, classical assumption tests, and simple linear regression tests. The results obtained in this research are that 98% of students who are still actively studying are members of the MBKM program, with the largest percentage being students majoring in biology. It was proven in this research that the MBKM program has a great influence on students' readiness to enter the world of work.